2015
DOI: 10.28945/2176
|View full text |Cite
|
Sign up to set email alerts
|

Learning Circles: A Collaborative Technology-Mediated Peer-Teaching Workshop

Abstract: This research study explores peer teaching and learning without a domain expert teacher, within the context of an activity where teams of second level students (~16 years old) are required to create a learning experience for their peers. The study looks at how participants would like to be taught and how they would teach their peers if given the opportunity and examines the support they require, their motivation levels, and if they actually learn curriculum content using this approach.An exploratory case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The NICE SCS format of delivery is based on students supporting and assisting each other's learning. Peer teaching has been successfully promoting students' learning in a multitude of areas, from physical education (Irvine, Williams & McKenna, 2016) to mathematics (Duah, Croft & Inglis, 2014) and from science (Sullivan, Marshall & Tangney, 2015) to philosophy (Butchart, Handfield & Restall, 2009). However, it is in medicine and in other health related sciences that peer teaching has been most productively applied (Hall et al, 2014;van de Mortel, Silberberg, Ahern & Pit, 2016;Rashid, Sobowale & Gore, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The NICE SCS format of delivery is based on students supporting and assisting each other's learning. Peer teaching has been successfully promoting students' learning in a multitude of areas, from physical education (Irvine, Williams & McKenna, 2016) to mathematics (Duah, Croft & Inglis, 2014) and from science (Sullivan, Marshall & Tangney, 2015) to philosophy (Butchart, Handfield & Restall, 2009). However, it is in medicine and in other health related sciences that peer teaching has been most productively applied (Hall et al, 2014;van de Mortel, Silberberg, Ahern & Pit, 2016;Rashid, Sobowale & Gore, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The idea of using students as peer-teachers is not exceptional (e.g., Lang et al, 2017). Sullivan et al (2015) reported the experiences of students teaching other students in ICT skills. However, their context differs from the situation described in this article.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…(cf. Sullivan, Marshall, & Tangney, 2015;Downes, 2006;Siemens, 2005;Davis, Edmunds, & Kelly-Bateman, 2008).…”
Section: Study Circles On Facebook Online Study Circlesmentioning
confidence: 99%